2021
DOI: 10.1108/lht-03-2021-0113
|View full text |Cite
|
Sign up to set email alerts
|

The aftermath of COVID-19 pandemic period: barriers in implementation of social distancing at workplace

Abstract: PurposeThe study aims to investigate the barriers in implementing social distancing at the workplace as an aftermath of the COVID-19 pandemic period.Design/methodology/approachStudy design consists of a review of literature, data collection and analysis. It encompasses identification, verification and analysis of the relationships among the barriers. Data have been collected from a panel of experts on matrix-type questionnaires from workplaces. Interpretive structural modeling (ISM) augmented with “Matrice d' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…For example, the variance of the incremental sample for every new wave may be correlated with some 'type' of countries added, which may affect overall variance. Another potential channel affecting variance across cross-sections may be shocks, such as Covid [65][66][67][68][69][70] in Wave 7, in which a tighter distribution of distrust is likely. The priors show microfinance intensity to be associated with distrust in poor as well as the ultra-poor according to all 3 measures of microfinance intensity.…”
Section: Plos Onementioning
confidence: 99%
“…For example, the variance of the incremental sample for every new wave may be correlated with some 'type' of countries added, which may affect overall variance. Another potential channel affecting variance across cross-sections may be shocks, such as Covid [65][66][67][68][69][70] in Wave 7, in which a tighter distribution of distrust is likely. The priors show microfinance intensity to be associated with distrust in poor as well as the ultra-poor according to all 3 measures of microfinance intensity.…”
Section: Plos Onementioning
confidence: 99%
“…For starters, the SE’s social goal lies between for-profit and non-profit organizations [ 12 , 20 ]. Second, social entrepreneurs are classified as social innovators who develop new products, services, and technology to address a social need [ 21 , 22 ]. The third factor is social networks, which are linked groups of individuals and organizations that share information and resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed a positive correlation between the two. Lastly, Abbass et al (2022) found ten barriers to implementing social distancing at the workplace. Readers may also be interested in Kumar et al (2021), who attempted to simulate people's interaction due to economic reopening, concerning confirmed cases at various places as per changing situation has been made using data obtained from India at the early stage of COVID-19.…”
Section: The Aftermath Of Covid-19 Pandemicmentioning
confidence: 99%